OP0298 PCSK9 IN ATHEROSCLEROTIC INFLAMMATION OF LUPUS PATIENTS AND MURINE MODEL OF LUPUS WITH ATHEROSCLEROSIS. (June 2019) - Fang, Chenglong; Luo, Tingting
Abstract : Background: Systemic lupus erythematosus (SLE) patients have tendencies of accelerated atherosclerosis (AS), which is refractory to statins. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a new therapeutic target for AS for its dual mechanisms in lipids metabolism and inflammation. PCSK9 inhibitors had proved to be highly promising cardiovascular disease (CVD) drugs [1]. Our previous study suggested that Toll-like recetor 4(TLR4) signal participates in the atherosclerotic inflammation of murine model of lupus with AS [2]. Objectives: To investigate the role of PCSK9 in atherosclerotic process of lupus and the association between TLR4 and PCSK9 in athergenic inflammation of murine model of lupus with AS. Methods: 90 SLE patients and 50 healthy controls were included. According to carotid intima-media thickness (cIMT), SLE patients were further divided into SLE-AS and SLE-NonAS subgroups (cut-off point: 1.0mm). Traditional CVD risk factors, inflammatory biomarkers and PCSK9 concentrations were compared between: (I) SLE patients and controls; (II) SLE-AS subgroup and SLE-NonAS subgroup. Correlational analysis and multivariate linear regression analysis were applied to analyze the association between PCSK9 levels and disease parameter, and the predictors of PCSK9 levels in SLE patients. Effects on PCSK9 concentrations by monotherapy with hydroxychloroquine (HCQ), which is thought having protective effects against CVD in SLE, were investigated by follow-up analysis in 15 SLE patients with inactive disease (SLEDAI=2). In animal experiment, murine model of SLE with AS was set up by intraperitoneally injection of lipopolysaccharides (LPS) in ApoE-/- mice. 30 female ApoE-/- mice were respectively administrated with LPS (SLE+AS group, n=10), saline (AS group, n=10) and LPS plus injection of lentiviruse-PCSK9 small hairpin RNA targeting the mouse PCSK9 gene into the tail vein to interfere PCSK9 expression (SLE+AS+PCSK9i group, n=10). 10 female C57BL/6 mice were included as controls. Serum concentrations of PCSK9 and inflammatory biomarkers including TNF-α and IL-1β, atherosclerotic lesion, lipids parameters, expression of PCSK9, TLR4 and NF-κB p65 in atherosclerotic plaque were assessed. Results: Characteristics of SLE patients and controls were listed in Table 1. SLE patients had significantly elevated serum PCSK9 levels than controls, especially in SLE-AS subgroup, accompanied with higher ratio of cIMT thickening. Correlational analysis showed PCSK9 concentrations correlated with C-reactive protein (CRP) levels, age and erythrocyte sedimentation rate (ESR), but not lipids parameters. Univariate and multivariate linear regression revealed that only CRP, but not age or ESR was positive predictors of PCSK9. Monotherapy with HCQ for 3 months significantly reduced PCSK9 levels in inactive SLE patients (Table 2, Figure 1). Mice in SLE+AS group had significantly higher serum PCSK9 concentrations than mice in AS group and C57BL/6 mice. Immunohistochemistry showed that PCSK9 overexpression was observed in SLE+AS mice than those in AS group and SLE+AS+PCSK9i group. Mice in SLE+AS+PCSK9i group exhibited decreased inflammatory cell infiltration in atherosclerotic plaque, alleviated atherosclerotic lesion, lower serum TNF-α and IL-1β levels and attenuated expression of TLR4 and NF-κB p65 in atherosclerotic plaque than SLE+AS group. PCSK9 silencing had no significant effects on lipids parameters in SLE+AS mice (Figure 2). Conclusion: PCSK9 participates in atherogenic inflammation in SLE patients and murine model of SLE with AS. This process is associated with TLR4-NF-κB pathway, probably independent of lipids parameters alteration. HCQ can effectively reduce PCSK9 levels in SLE patients. References: [1] Sabatine MS, et al. N Engl J Med. 2017, 376(18):1713-1722. [2] Ni JQ, et al. Clin Dev Immunol. 2013;2013:476856. Disclosure of Interests: None declared